Penerapan Prinsip Extraterritorial Jurisdiction Dalam Memerangi Tindak Pidana Siber - Rusdianto Rusdianto; Muh. Risnain (Mataram Journal of International Law, 2023)
This research aims to determine the development of the regulation of extraterritorial jurisdiction principles in combating cybercrime and the application of extraterritorial jurisdiction principles. The research method used is normative research. The approach used is statutory, historical, and conceptual. The sources of legal material used are primary, secondary, and tertiary. The legal material collection technique used is in the form of library data. The analysis of legal materials used is a qualitative analysis method. The study result shows that the development of the principle of extraterritorial jurisdiction regulation began with the birth of rules in background paper documents, then the emergence of the 1996 European Council regulations. Applying the principle of extraterritorial jurisdiction is urgently needed in combating criminal acts when cases intersect with state jurisdiction. So that a country can choose jurisdictional principles that can apply in resolving cases, such as the example of the case conducted by Abraham Ben Moses in the United States. Namely, law enforcement can be carried out in Indonesia based on active national principles and protection principles following the ITE Law and the Criminal Code.